The Accuracy and Clinical Utility of Intraoperative Frozen Section Analysis in Open Biopsy of Bone. Issue 11 (1st June 2019) - Wallace, Matthew T.; Lin, Patrick P.; Bird, Justin E.; Moon, Bryan S.; Satcher, Robert L.; Lewis, Valerae O.
Abstract : Background: Open biopsy of bone is the diagnostic benchmark for the diagnosis of skeletal lesions. Intraoperative pathology consultation with frozen section analysis is commonly performed to confirm adequacy of lesional tissue and guide intraoperative decision making. The purpose of this study was to determine the accuracy and clinical utility of intraoperative frozen section during open bone biopsy. Methods: A retrospective review of 485 open biopsies of osseous lesions from 474 patients between 1997 and 2014 was performed. Pathology reports, operative notes, and prebiopsy imaging were assessed to determine the accuracy rates of frozen section analysis compared with final pathology. Pearson chi-squared and Fisher exact tests were performed to compare the accuracy and clinical utility rates based on soft-tissue extension, previous biopsy, lesional consistency, disease, and location. Results: Overall diagnostic yield of open bone biopsy was 95.3%. Frozen section analysis was accurate in 54.2%, equivocal positive in 21.2%, equivocal negative in 21.0%, and incorrect in 3.5% of cases. Previous nondiagnostic biopsy and the type of disease were found to have statistically significant effects on the accuracy of frozen section analysis. Conclusion: Frozen section analysis was diagnostic in approximately one half of open biopsy cases. Additional information in equivocal positive results suggests that frozen section analysis is helpful for intraoperative decision making (clinical utility) in 75.4% of cases. Level of Evidence: Retrospective review level IV